1980
DOI: 10.1121/1.384753
|View full text |Cite
|
Sign up to set email alerts
|

Computer studies on parametric coding of speech spectra

Abstract: We report a series of computer experiments aimed to increase our understanding about the sufficiency of the short-time amplitude spectrum for speech coding, and to examine how bandpass segments of the speech spectrum might be represented parametrically. For this purpose we utilize the absolute value of the short-time Fourier transform and the time-derivative of the short-time phase, evaluated at frequency intervals chosen according to auditory criteria. We analyze and digitally encode these parameters. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…of a jixed filter bank. The amplitude, frequency, and phase measurements of the filter outputs are then used in various configurations of speech synthesizers [7]. Although the present work is based on the discrete Fourier transform (DFT), which can be interpreted as a filter bank, the use of a high-resolution DFT in combination with peak picking renders a highly adaptive filter .…”
Section: Discussionmentioning
confidence: 99%
“…of a jixed filter bank. The amplitude, frequency, and phase measurements of the filter outputs are then used in various configurations of speech synthesizers [7]. Although the present work is based on the discrete Fourier transform (DFT), which can be interpreted as a filter bank, the use of a high-resolution DFT in combination with peak picking renders a highly adaptive filter .…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, however, one has to decide on a time-frequency scale at which to calculate the amplitude envelopes. In psychophysical experiments, the scale is often chosen by using filters with a one-fourth octave bandwidth because this value matches the measured critical band of audition in humans (Flanagan and Christensen, 1980;Drullman, 1995). Shannon and colleagues have also shown that speech comprehension increases rapidly as the number of frequency bands is increased from one very wide band to a small number of still relatively wide bands, emphasizing the relative importance of temporal structure over spectral structure in speech comprehension (Shannon et al, 1995).…”
Section: Time-frequency Tuning Of Hvc Neurons and Speech Psychophysicsmentioning
confidence: 99%
“…Presumably, some of these difficulties were related to the method used to produce the auditory filtered spectra (see Method section). Further re-search will employ more direct methods of deriving the auditory filtered display, such as those proposed by Klatt (1976Klatt ( , 1979 and Flanagan and Christensen (1980). For example, direct filtering would result in a shortening of the, analysis time window for highfrequency energy.…”
Section: Discussionmentioning
confidence: 99%